Willingness-to-pay and willingness-to-accept of informal caregivers of dependent elderly people in Shanghai, China - Wenwei Liu; Tongzhou Lyu; Xiaoyi Zhang; Suwei Yuan; Huimin Zhang (BMC, 2020)
Abstract Background In order to make optimal long-term care-related decisions, it is important to take a societal perspective. Shanghai is one of the pilot cities of social long-term care insurance in China. However, little knowledge exists about the economic value of the informal care provided to dependent elderly people in China. This paper aims to evaluate the economic value of informal caregiving in Shanghai using the contingent valuation method by their least-preferred care tasks, and identify the associated factors of willingness-to-pay (WTP) and willingness-to-accept (WTA) of the informal caregivers. Methods This study employed the contingent valuation method to elicit 371 informal caregivers' WTP and WTA for 1 hour of reduction or increase of least-preferred caring tasks in Shanghai. Univariate and multivariate analyses were conducted to explore the associated factors with the WTP and WTA values. Results The average WTP and WTA were 25.31 CNY and 38.66 CNY, respectively. The associated factors with WTP include caregiver's income and caregiver's relationship to the recipient. Care recipient's age, income, least-preferred task by the caregiver, and subscales of Caregiver Reaction Assessment were found to be associated with WTA. The non-responsiveness rates were 26.1 and 33.2% for WTP and WTA questions, respectively. Conclusions The findings of the current study demonstrated that decision-makers and researchers should take the economic valuation results of informal care into account to make more informed and effective long-term care-related policies and analyses.